ANALISIS MISKONSEPSI SISWA KELAS XI MADRASAH ALIYAH NEGERI 1 (MAN 1) LAMPUNG TIMUR DALAM MEMPELAJARI POKOK BAHASAN TERMOKIMIA - Suyatman, Suyatman; Taher, Tarmizi (Universitas Negeri Semarang, 2020)
Thermochemistry as one of sub-subject in chemistry subject which is taught in senior high school. This subject has considered as one of the most difficult subject to be learn by student. In understanding thermochemistry, students often experience misconception because this subject is containing abstract concept and requires representation at the macroscopic, submacroscopic, and symbolic levels. This study was intended to determine the level of student understanding of thermochemical subject after going through the teaching and learning process as an evaluation material for students and teachers. The used research method was descriptive quantitative using a three-tier multiple choice (TTMC) diagnostic test instrument. The subjects of this study were students of class IX IPA 1 Madrasah Aliyah Negri 1 East Lampung in the academic year 2019/2020 with a sample size of 33 students. The obtained results exhibited that student misconception toward the tested subject, including exothermic and endothermic reaction, thermochemistry equation, enthalpy changes, Hess Law, and bonding energy, were 90, 78, 45, 66, and 18%, respectively. The results of the analysis are expected to be an evaluation material for teachers to be able to convey thermochemical material more conceptually to improve student understanding.